(untitled) (Journal of Nepal Geological Society, 1981)
To evaluate the geotectonics of the Kathmandu Block on the basis of lithology, stratigraphy and structures, observationsns were made along the two traverses lying east and west of the block. There exist an anticlinorium to the north and a synclinorium to the south of Kathmandu Valley which itself is a faulted anticline. The grade of metamorphism increases towards granites and the Main Central Thrust.